Improving students’ enthusiasm for learning English using animated video - Maria Jawa Open; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2022)
The study aimed at investigating the effectiveness of animated videos in improving students’ enthusiasm at SDK Sang Timur Yogyakarta and describing the improvement of students’ enthusiasm for learning English. The design of this research was Classroom Action Research (CAR) and the subject of this research was 25 students of the first graders of elementary school at SDK Sang Timur, located in Batikan, Yogyakarta. The observation indicated that students had difficulties in saying English words correctly and when they respond in the English language. Moreover, the result of cycle 1 showed that students’ enthusiasm for learning English got improved. Students still felt doubtful about responding to questions. They seemed to be excited about the video. In cycle 2, students’ enthusiasm improved. Students had a good recollection of the previous lesson when the researcher asked them about it. It also appeared that students became more active and enthusiastic about the lesson and seemed eager to learn more using animated videos. Therefore, it can be concluded that animated videos brought a positive learning environment and enthusiasm as they educated and entertained students at the same time. In short, an animated video was an effective tool for improving students’ motivation for learning English.